The preventive effect of atorvastatin on atrial fibrillation: a meta-analysis of randomized controlled trials - Yang, Qian (BioMed Central, 2014)
BACKGROUND: A number of clinical and experimental studies have investigated the effect of atorvastatin on atrial fibrillation (AF), but the results are equivocal. This meta-analysis was performed to evaluate whether atorvastatin can reduce the risk of AF in different populations. METHODS: We searched PubMed, EMBASE and the Cochrane Database for all published studies that examined the effect of atorvastatin therapy on AF up to April 2014. A random effects model was used when there was substantial heterogeneity and a fixed effects model when there was negligible heterogeneity. RESULTS: Eighteen published studies including 9952 patients with sinus rhythm were identified for inclusion in the analysis. Ten studies investigated primary prevention of AF by atorvastatin in patients without AF, seven studies investigated secondary prevention of atorvastatin in patients with AF, and one study investigated mixed populations of patients. Overall, atorvastatin was associated with a decreased risk of AF (odds ratio (OR) 0.51, 95% confidence interval (CI) 0.36–0.70, P < 0.0001). However, subgroup analyses showed that in the primary prevention subgroup (OR 0.55, 95% CI 0.38–0.81, P = 0.002), atorvastatin reduced the risk of new-onset AF in patients after coronary surgery (OR 0.44, 95% CI 0.29–0.68, P = 0.0002), but had no beneficial effect in patients without coronary surgery (OR 0.97, 95% CI 0.59–1.58, P = 0.89); in the secondary prevention subgroup, atorvastatin had no beneficial effect on AF recurrence in patients with electrical cardioversion (EC) (OR 0.57, 95% CI 0.25–1.32, P = 0.19) or without EC (OR 0.38, 95% CI 0.14–1.06, P = 0.06). CONCLUSIONS: This meta-analysis suggests that atorvastatin has an overall protective effect against AF. However, this preventive effect was not seen in all types of AF. Atorvastatin was significantly associated with a decreased risk of new-onset AF in patients after coronary surgery. Moreover, atorvastatin did not prove to exert a significant protective effect against the AF recurrences in both patients who had experienced sinus rhythm restoration by means of EC and those who had obtained cardioversion by means of drug therapy. Thus, further prospective studies are warranted.